600 sekund . 600 sekund . 600 Seconds . 600 секунд - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Criminal situation in Leningrad; demonstration of extrasensory abilities. Contributors: Nevzorov, Aleksandr (Anchor) Series description: A television program broadcasted in 1987-1993 on the St. Petersburg TV channel. Within 10 minutes, the program hosts described main events of the day in Leningrad/St. Petersburg and commented of video clips. Криминальная хроника Ленинграда; демонстрация экстрасенсорных способностей. Создатели: Невзоров, Александр (Ведущий/Ведущая) Описание серии: Телевизионная передача, выходившая в эфир в 1987-1993 гг. на петербургском телеканале. За 10 минут ведущие рассказывали об основных событиях дня в Ленинграде/Санкт-Петербурге.